Clinico-pathological analysis of oral squamous cell carcinoma in a period of 8 years in a hospital in South of Brazil - Freitas, Rayssa Ruas; Campos, Maria Martha; Koth, Valesca Sander; Ribeiro, Alice; Payeras, Marcia Rodrigues; Maito, Fabio Luiz; Carvalho, Ana Luísa (Journal of Oral Diagnosis, 2019)
Oral cancer is multifactorial disease with high morbidity and mortality rates. The knowledge of patient profiles with this neoplasm can help to determine the extension of the problem and guide public health policies. The present study aimed to identify the prevalence and to describe the clinico-pathological characteristics of oral squamous cell carcinoma, by means of medical records from Hospital São Lucas, at Pontifícia Universidade Católica do Rio Grande do Sul. Medical records from fifty-six patients consulted between 2007 and 2015 were included. Data from age, sex, race, occupation and residence, tobacco and alcohol consumption, tumor characteristics, treatment and clinical outcomes were analyzed. The sample presented a mean age of 59.37 (±10.997) years and the majority were males (4.6:1 male: female ratio), Caucasians (87.5 %), living in an urban area (56.4%). In this study, 80.00 % of participants declared to be smoker or former smokers, while 51.8 % declared to be alcoholics or former alcoholics. The lip was the most involved anatomic site (33.9 %). Regarding the tumor characteristics, most of them were classified as T3/T4 (41.1 %), with an involvement of regional lymph nodes (35.7 %) and histologic grading I/ II (60.7 %). Our results indicate that oral cancer continues to show late diagnosis, which leads to invasive treatment, negatively influencing in patients survival. For the success of studies like this, it is crucial to fill in the medical records completely and legibly.